2017
DOI: 10.1002/adhm.201700978
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Enhances Serum Stability of Bioreducible Poly(amido amine) Polyplexes and Enables Efficient Intravenous siRNA Delivery

Abstract: The use of small interfering RNA (siRNA) in cancer treatment has been limited by the lack of effective systemic delivery methods. Although synthetic polycations have been widely explored in siRNA delivery, polycation/siRNA polyplexes often suffer from insufficient stability in vivo. Here, rationally designed siRNA delivery systems that meet the requirements for systemic siRNA delivery to distant tumors are reported. The hypothesis that modular design of delivery systems based on poly(amido amine)s that combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…It was also observed that FP2k0.75 showed the highest GFP expression among FP2ks, similarly with luciferase assay result. As other research groups reported (Cai et al, ; Cai, Zhu, Zhang, & Gu, ; Chen et al, , ; Gong et al, ; He et al, ; Liu et al, ; Lv et al, ; Wang et al, ; Wang & Cheng, , ; Wang, Wang, et al, ; Xiao et al, ) improvement of transfection efficiency and serum tolerance by fluorination was revealed in this study. Taken together with the cytotoxicity result, it is concluded that fluorination is double‐edged sword for polymeric gene delivery systems because strong interaction with cellular membrane and penetration into the membrane can cause both high cytotoxicity and transfection efficiency.…”
Section: Discussionsupporting
confidence: 81%
“…It was also observed that FP2k0.75 showed the highest GFP expression among FP2ks, similarly with luciferase assay result. As other research groups reported (Cai et al, ; Cai, Zhu, Zhang, & Gu, ; Chen et al, , ; Gong et al, ; He et al, ; Liu et al, ; Lv et al, ; Wang et al, ; Wang & Cheng, , ; Wang, Wang, et al, ; Xiao et al, ) improvement of transfection efficiency and serum tolerance by fluorination was revealed in this study. Taken together with the cytotoxicity result, it is concluded that fluorination is double‐edged sword for polymeric gene delivery systems because strong interaction with cellular membrane and penetration into the membrane can cause both high cytotoxicity and transfection efficiency.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that the cytotoxicity of polycations increases with an increase in molecular weight of polymers . For example, PEI with molecular weight greater than 10 000 g mol −1 showed possible toxicity at 50 µg mL −1 toward human epithelial osteosarcoma U2OS cells, while the PEI with molecular weight 25 000 g mol −1 exhibited high toxicity at 10 µg mL −1 toward NIH 3T3 mouse fibroblasts and human aortic endothelial cells . However, PEADs and mPEG350‐PEADs synthesized with molecular weight lesser than 4000 g mol −1 did not show any toxicity up to 200 µg mL −1 , and exhibit higher protein loading efficiency (>95%) (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Another avenue is the use of ‘smart’ polymers that respond to changes in the biological environment. For example, Chen and colleagues [ 42 , 43 ] evaluated the effect of fluorination and the bioreducibility of cationic hyperbranched poly(amido amines). Reducible fluorinated polymers complexed well with siRNA and induced superior gene knockdown compared with nonreducing polyplexes following intravenous and tumoral injection in mice.…”
Section: Delivery Of Gene Therapies To the Skinmentioning
confidence: 99%